Incidence, risk factors, and mortality of atrial fibrillation in breast cancer: a SEER-Medicare analysis. (14th November 2021) - Guha, Avirup; Fradley, Michael G; Dent, Susan F; Weintraub, Neal L; Lustberg, Maryam B; Alonso, Alvaro; Addison, Daniel
Abstract: Aims: The national incidence, risk factors, and associated mortality of atrial fibrillation (AF) in breast cancer patients are unknown. Methods and results: Using the Surveillance, Epidemiology, and End Results-Medicare-linked database, we identified females, ≥66 years old, with a new primary diagnosis of breast cancer from 2007 through 2014. These patients were individually matched 1:1 to Medicare enrolees without cancer, and each pair was followed for 1 year to identify a primary outcome of AF. Cumulative incidence was calculated using competing risk survival statistics. Following this, identifying risk factors of AF among breast cancer patients was conducted using the adjusted Cox proportional hazards model. Finally, Kaplan–Meier methods and adjusted Cox proportional hazards modelling were performed to estimate mortality in breast cancer patients with incident and prevalent AF. This study included 85 423 breast cancer patients. Among these 9425 (11.0%) had AF diagnosis prior to the breast cancer diagnosis. New-onset AF was diagnosed in 2993 (3.9%) patients in a 1-year period after the breast cancer diagnosis [incidence 3.3%, 95% confidence interval (CI) 3.0–3.5%, at 1 year; higher rate in the first 60 days (0.6%/month)]. Comparatively, the incidence of new-onset AF in matched non-cancer controls was 1.8% (95% CI 1.6–2.0%). Apart from traditional demographic and cardiovascular risk factors, breast cancer stage was strongly associated with the development of AF [American Joint Committee on Cancer (AJCC) Stage II/III/IV vs. I: adjusted hazard ratio (aHR) 1.51/2.63/4.21, respectively]. New-onset AF after breast cancer diagnosis (aHR 3.00) is associated with increased 1-year cardiovascular mortality. Conclusion: AF incidence is significantly higher in women after a breast cancer diagnosis. Higher breast cancer stages at diagnos are significantly associated with a higher risk of AF. New-onset AF in the new breast cancer diagnosis setting increases 1-year cardiovascular mortality but not breast cancer-related mortality. Key Question: What are the incidence, prevalence, risk factors and mortality outcomes of atrial fibrillation (AF) in a multi-ethnic representative United States cohort of breast cancer patients? Key Finding: Annual incidence for AF is 3.9% with highest rate in the first 60 days after cancer diagnosis. Cancer stage and grade are the strongest risk factors for AF. New onset AF after breast cancer increases all-cause and cardiovascular mortality. Take Home Message: AF incidence is higher in breast cancer patients and is associated with later stage and grade at diagnosis of breast cancer. Involving cardio-oncology in those who develop AF after cancer diagnosis should be encouraged to improve their cardiovascular and overall prognosis. Graphical Abstract: